Assessment of corrosion in retrieved spine implants. Issue 2 (9th March 2017) - Panagiotopoulou, V. C.; Hothi, H. S.; Anwar, H. A.; Molloy, S.; Noordeen, H.; Rezajooi, K.; Sutcliffe, J.; Skinner, J. A.; Hart, A. J.
ABSTRACT: Recently the use of dissimilar metals in spine instrumentation has increased, especially in the case of adult deformities, where rods made from Cobalt Chrome alloys (CoCr) are used with Titanium (Ti) screws. The use of dissimilar metals increases the risk of galvanic corrosion and patients have required revision spine surgery due to severe metallosis that may have been caused by corrosion. We aimed to assess the presence of corrosion in spine implant retrievals from constructs with two types of material combinations: similar (Ti/Ti) and dissimilar (CoCr/Ti). First, we devised a grading score for corrosion of the rod‐fixture junctions. Then, we applied this score to a collection of retrieved spine implants. Our proposed corrosion grading score was proven reliable (kappa > 0.7). We found no significant difference in the scores between 4 CoCr and 11 Ti rods ( p  = 0.0642). There was no indication that time of implantation had an effect on the corrosion score ( p  = 0.9361). We recommend surgeons avoid using implants designs with dissimilar metals to reduce the risk of corrosion whilst a larger scale study of retrieved spine implants is conducted. Future studies can now use our scoring system for spine implant corrosion. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 632–638, 2018.